Kursi Karakter Ergonomi Sebagai Pendorong Minat dan Kenyamanan Belajar Siswa Sekolah Madrasah Tarbiyatul Islamiyah - Rofian, Rofian; Prasetyo, Singgih Adhi; Naufal, Gostsa Khusnun; Budiyanto, Ari Eko (JGEN : Jurnal Pengabdian Kepada Masyarakat, 2024)
Madrasah Tarbiyatul Islamiyah School, located in Blora district, is a religion-based school located on the border between the city and village districts. This madrasah school has tables and chairs that do not accommodate student ergonomics. Inappropriate designs for early childhood also cause students to be less interested in participating in the teaching and learning process. The urgency faced by the Madrasah Tarbiyatul Islamiyah school is: (1) the chairs used for the teaching and learning process lack ergonomics, (2) the design of the chairs cannot attract students' interest in participating in the teaching and learning process, (3) the need to collaborate with schools very much, as improving the quality of schools. The objectives and solutions offered are: (1) designing chairs that can accommodate student ergonomics and increase student interest during the teaching and learning process, (2) provide an understanding of the importance of collaborating with school parties, as a need for creative education in schools through extracurricular learning, (3) Monitoring and Evaluation which will be carried out throughout the implementation and after PKM as a form of sustainable partnership. This PKM is related to the MBKM program involving 3 students with the potential for recognition in the lectures they have taken. The outputs of PKM activities are (1) Scientific publication in the National Journal of Community Service Abdimas, in 2024; (2) Publication of news in online or print mass media within the Central Java region, publication in 2024; (3) Registration of IPR for product design and manufacture of ergonomic character chair products.